Motivation psychological characteristics of canoe-kayak sprint elite youth athletes - Bebetsos, E.; Aggelakis, E.; Bebetsos, G.; Gargalianos, D. (Physical Culture and Sport. Studies and Research, 2020)
Scientists (Spielberger, 1989; Mauss & Robinson, 2009) documented that anxiety does not exist as a single cognitive-emotional and physiological state, and suggested to differentiate it as: a) state anxiety, where it was reported, in subjective, as conscious perceptions of anxiety and tension, accompanied or associated with activation or stimulation of the autonomic nervous system, and b) anxiety as a personality trait or trait anxiety, where reference was made to an acquired behavioral predisposition, where an individual perceives a large number of objectively non-threatening situations as threatening and respond to them with occasional anxiety reactions disproportionate to the size of the objective risk. Predisposing anxiety suggested relative permanent differences in an individual's anxiety tendency, which was a characteristic of his personality. Existing individual differences were the ones that determined what stimuli were rated as threatening. The objective of the current study was the investigation of anxiety and satisfaction levels among Elite Greek Youth athletes of Canoe-Kayak Sprint. Additionally, whether elements such as gender, age, athletic experience, and weekly practice-time, differentiated the sample. 122 athletes, (61 males and 61 females) between the ages of 15-17 yrs. old, who competed in the Hellenic Federation`s Canoe-Kayak Sprint National Championships. Study participants were invited to complete two questionnaires: a) the Greek version of "CSAI-2" (Stavrou, Zervas, Kakkos, & Psichoundaki, 1998), and b) the Greek version of the "Athlete Satisfaction" scale (Bebetsos & Theodorakis, 2003). Results of the conducted study revealed that the sample differentiated: a) on somatic, and cognitive anxiety, according to their athletic experience, and b) on somatic, and cognitive anxiety, self-confidence, leadership, and personal outcome, according to their weekly practice-time. Finally, no sex differences were found in any questionnaire variable. In conclusion, the survey results highlighted the importance of the psychological factors tested on Canoe-Kayak Sprint athletes` performance. Knowing and understanding athletes` psychological state, can help them out (the athletes) in identifying aspects such as stress and satisfaction that directly affect their racing performance.